2014
DOI: 10.1186/1471-2466-14-186
|View full text |Cite
|
Sign up to set email alerts
|

COPD Assessment Test (CAT) score as a predictor of major depression among subjects with chronic obstructive pulmonary disease and mild hypoxemia: a case–control study

Abstract: BackgroundDepression is a common comorbidity among patients with Chronic Obstructive Pulmonary Disease (COPD) and has a significant impact on the course of the disease. The aim of this study is to determine association between COPD Assessment Test (CAT) and major depression among clinically stable out-patient COPD subjects with mild hypoxemia.MethodsCase–control study. Cases were 30 patients with major depression and controls were 30 patients without depression. Major depression was diagnosed according to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 32 publications
2
11
0
1
Order By: Relevance
“…The higher the number of co-morbidities the higher was the total CAT score. Moreover, it has been shown that CAT scores elevated with the presence of depression (Silva Júnior et al, 2014). We also noticed that patients with depression who currently using antidepressant, had higher scores with the item 'having energy.'…”
Section: Discussionsupporting
confidence: 51%
“…The higher the number of co-morbidities the higher was the total CAT score. Moreover, it has been shown that CAT scores elevated with the presence of depression (Silva Júnior et al, 2014). We also noticed that patients with depression who currently using antidepressant, had higher scores with the item 'having energy.'…”
Section: Discussionsupporting
confidence: 51%
“…Daily smoking has been shown to be a risk factor for depression, and prior depression predisposes to new depression . A relationship between CAT scores >20 and depression has been reported previously . Furthermore, the perception of dyspnoea is related to psychological factors, meaning that symptoms of depression increase dyspnoea .…”
Section: Discussionmentioning
confidence: 82%
“…The BDI score alone explained 31% of the variance of CAT, and a cutoff of 20 units identified major depression with an odds ratio of 7.88. 25 …”
Section: Discussionmentioning
confidence: 99%